الإجماع والاستصحاب في دراسة أصول النحو - Noza Aflisia; Ahmad Fikri (UIN Fatmawati Sukarno Bengkulu, 2021)
The two sources of nahwu, namely Ijma and Istishab are very important to study After Sama and Qiyas. This paper will discuss in more detail regarding Ijma and Istishab. So that Arabic learners, especially nahwu not only understand the existing nahwu rules, but also understand the origin of these rules. The Library Research is using referrals from various sources such as books and scientific articles. The data collection technique is to conduct a review of these books and journals. The data obtained are then processed by analytic descriptive techniques. The results showed that these two sources were at the bottom of the nahwu source, even if istishab was believed to be the weakest source compared to the other three sources. This situation does not reduce the urgency of this study. If ijma is based on the agreement of the nahwu ulama, then istishab again refers to the original provisions in nahwu matters that are not found in other nahwu sources. Ijma lughawi is divided into three types, namely Ijma Arabs, Ijma experts of Nahwu, and Ijma Ruwat. Meanwhile, Istishab occurs in sounds, words and sentences. There are two parts in istishab, namely Ushl al-Wadh'i or also known as the original rules, and Al-'Udul or lafadz which is returned to the original rules.